Isadora Moon and the shooting star - Muncaster, Harriet (Muncaster, Harriet. Isadora Moon., 2021)
Isadora Moon is special because she's different. Her mum is a fairy and her dad is a vampire and she's a bit of both. Isadora is observing the night sky for a school project - her class is learning everything about space and she decides to look at the stars for inspiration. But wait, what is that? Through the telescope, Isadora spots a shooting star that falls to Earth! After courageously finding the place where the star landed, Isadora discovers a new twinkling friend. Her name is Nova, she is a Glow Sprite and she is not supposed to be there. Even worse, Nova's moon kitten Pluto is lost and she needs Isadora's help to find him. Between magical campfires, space lessons, moon cheese and a glowing sleepover, Isadora will need to use all her wits to help Nova finding Pluto before her new friend has to fly back to the stars. Beautiful gift edition with silver sprayed edges and packed with extra activities and things to make and do.